Pengelolaan Wilayah Perbatasan Berbasis Integrated Border Management (IBM) dalam Meningkatkan Daya Saing Investasi dan Perdagangan Indonesia - Ade Priangani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2014)
Position of Indonesia-Singapore borders are ais very strategic, such a position, however, has not been optimally utilized. Borders area is an enticingentrance for investors. Accordingly, there will be a need of integrated management so as to be able to improve competitiveness mainly in the field of investment and trade. The reason why management model more suitably refers to the IBM because the model in some countries has successfully maximized function o fborders area. This research aims to study and give input into implementation of Border Management mainly Integrated Border Management (IBM) in the area of Indonesia Borders, especially Indonesia-Singapore Borders, as an effort to promote Indonesia competitiveness in the sector of trade and investment. This research employs single case study qualitative analysis approach. The research focuses on the making of competitiveness of investment and trade in Indonesia’s borders region (Riau Island), referring to IBM and competitiveness parameter so as to be towards single face inborders management in borders area. Location of doing research is Batam and Tanjungpinang. Informen are involved in this study could be Secretary and Staff of Borders Management Board of Riau Island Province, Workers of Riau Island Immigration Office, Tanjungpinang City Customs Office, BP-Batam, PT KSP and expert judgment Prof. Asep Warlan, Prof. Rusadi Kantaprawira and Agus GK (Komisi I DPR-RI) The results of the research demontrated that: (1) Impediments to Indonesia-Singapore (Batam-Bintan) Border Area Management are lack of manpower owned by Border Management Board of Riau Islands Province, increasingly global trade, lack of law and regulations of borders, (2) IBM based- border are a management has been running, however has not been so adequate in line with challenges of current border management, (3) Mechanism of trade and company permissions to run all their business transactions are done through one office, whereas investment procedure in Indonesia-Singapore border area is done through one roof policy, (4) Implementation of Integrated Border Management principle to management of border in the area of Indonesia-Singapore border has referred to the emerging of Single Administrative Document (SAD) and Single Window (SW), however implementation of Single Window in the area of Indonesia-Singapore border has not been optimal. The results of the research might contribute to development of management science mainly border management, and might be are ference to implementation of border area management strategy done by National Board of Border Management, in special Border Management Board of Riau Islands Province by referring to IBM (SAD and SW) insearch of moving towards single face in border management.